2019
DOI: 10.1017/pasa.2019.44
|View full text |Cite
|
Sign up to set email alerts
|

Study of the 13CO/C18O abundance ratio towards the filamentary infrared dark cloud IRDC 34.43 + 0.24

Abstract: Nowadays, there are several observational studies about the 13CO/C18O abundance ratio ( $X^{13/18}$ ) towards nearby molecular clouds. These works give observational support to the C18O selective photodissociation due to the interaction between the far ultraviolet (FUV) radiation and the molecular gas. It is necessary to increase the sample of molecular clouds located at different distances and affected in different ways by nearby or embedded H ii regions and OB associations to stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Values 3 − 10 have been reported in dark clouds and high-mass star-forming regions alike (Paron et al 2018;Areal et al 2018;Roueff et al 2021). In our simulations, the ratio is [ 13 CO]/[C 18 O]=6.67, which is close to the average values found in IRDCs (Du & Yang 2008;Areal et al 2019). Pirogov et al (1995) reported an average value [HCO + ]/[H 13 CO + ]=29 for a sample of dense clouds.…”
Section: Radiative Transfer Modellingsupporting
confidence: 89%
“…Values 3 − 10 have been reported in dark clouds and high-mass star-forming regions alike (Paron et al 2018;Areal et al 2018;Roueff et al 2021). In our simulations, the ratio is [ 13 CO]/[C 18 O]=6.67, which is close to the average values found in IRDCs (Du & Yang 2008;Areal et al 2019). Pirogov et al (1995) reported an average value [HCO + ]/[H 13 CO + ]=29 for a sample of dense clouds.…”
Section: Radiative Transfer Modellingsupporting
confidence: 89%
“…T bg = 2.73 is the background temperature, and T mb dv represents the integrated intensity. In the above formulas, the correction for high optical depth was applied (Frerking et al 1982;Goldsmith et al 2008;Areal et al 2019). Assuming the 12 CO emission to be optically thick, we can estimate the excitation temperature T ex following the formula (Garden et al 1991;Pineda et al 2008)…”
Section: Molecular Linementioning
confidence: 99%
“…T bg = 2.73 K is the background temperature and T mb dv represents the integrated intensity. In the above formulas, the correction for high optical depth was applied (Frerking et al 1982;Goldsmith et al 2008;Areal et al 2019). Assuming optically thick emission of HCO + (1-0) emission, we can estimate the excitation temperature, T ex , following the formula (Garden et al 1991;Pineda et al 2008)…”
Section: Appendix A: Lte Analysismentioning
confidence: 99%